Wireless body-area network monitoring with ZigBee, 5G and 5G with MIMO for outdoor environments - Ahmed Mohammed Qasim Kamil Al-Asadi; Karrar Shakir Muttair; Ahmed Ghanim Wadday; Mahmood Farhan Mosleh (Institute of Advanced Engineering and Science, 2022)
Wireless body area network (WBAN) works near or inside the human body and is characterized by its accuracy in sending and receiving data. It works for long hours and must be low in energy consumption. One of its problems is that the transmission and reception distance is few and does not exceed a few meters. We worked on simulations based on a network consisting of ZigBee or fifth-generation (5G) and 5G with multiple-input and multiple-output (MIMO) nodes to deliver information to the center (hospital) at a 2.4 to 2.8 or 5 GHz frequency to solve this problem. Suppose the sensors are connected to the Arduino, which in turn is connected to the transmitter connection. The proposed method transmits data obtained from the sensor that touched the patient by multi-node to the hospital. The suggested method shows the best scenario to reduce energy consumption based on the number of active nodes. Based on the results obtained, we have noticed that ZigBee devices reduce energy use, perform better, and significantly extend the life of the nodes. While 5G devices increased the response speed in transferring data. In addition, MIMO antennas have the advantage of adding more stability in the connection between nodes.